Pilot-scale composting for organic solid waste generating solid and liquid biofertilizers and bedding material (Research, Society and Development, 2024)
This investigation aimed to develop and execute a pilot-scale project for an organic solid waste composting yard. To this end, three types of composting windrows (n=3) — specifically, without soil waterproofing and with waterproofing with canvas or masonry — were constructed, and wet household solid waste (RSDU) and public waste (RPU) were disposed of in them. The humidity, nitrogen, and TOC data were 48±3% and 89±3%; 0.93±0.04% and 1.01±0.05%; and 45.3±4.7% and 52.84±0.04% for RSDU and RPU, respectively. The core temperature values in the stacks were similar at different sampling times. A pilot composting yard was implemented at the University of Sorocaba, proving the feasibility of adequately disposing of part of the solid waste generated on the Campus. Despite the composting time and temperature being similar in the three types of windrows, windrows with a masonry structure showed an advantage in capturing liquid biofertilizer. In maintaining the moisture content in the windrows, irrigation with water was unnecessary due to the temperatures of the composting process, promoting the release of water from the waste. Establishing the periodicity of windrow aeration proved essential in promoting the composting process. Furthermore, it was observed that even the low frequency of changes carried out to maintain the oxygenation of the medium was sufficient to maintain the ideal temperature and humidity for the microbiota until the compost maturation phase.